Polipectomía gástrica por vía endoscópica - Celestino F., Álvaro (1979)
The endoscopic polypectomy using high frecuency current was performed to remove elevated lesions of the stomach in 13 patients, 9 male and 5 female, between 28 to 68 years old. The gross appearance of 16 elevated lesions removed by snare excision was classified on the basis of Yamada's classification. The final histopathologic diagnosis was: 10 hiperplasic polyps, 5 adenomatous polyps and 1 aberrant pancreas. The post polypectomy ulceration healed between 2 to 4 weeks without complications during and after the procedure.